AVALIAÇÃO DA COMPOSIÇÃO QUÍMICA E DOS POTENCIAIS DE TINTURAS DOS CAULES DE ESPÉCIES DO GÊNERO Campomanesia - Da Silva, Mateus Ricardo; De Castro, Thiago Luis Aguayo; Da Silva, Juliana Ketlin Moro; Cardoso, Claudia Andrea Lima (ANAIS DO ENIC, 2025)
.